(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Breast cancer is one of the most common and life-threatening diseases among women worldwide. Early diagnosis plays a crucial role in increasing survival rates and improving treatment effectiveness. This article presents the key factors of prediction and analysis that are essential for developing algorithms and software tools for the early detection of breast cancer using artificial intelligence (AI) and machine learning (ML) techniques.